PENERAPAN STRATEGI PROMOSI DALAM MENINGKATKAN PENJUALAN HOLYCOW! STEAKHOUSE BY CHEF AFIT SURABAYA - Ramadhan, Syahwa; Samsudin, Acep (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
The research in this thesis aims to determine the appropriate promotion strategies to be implemented by Holycow! Steakhouse by Chef Afit Surabaya in increasing sales. This study adopts a qualitative descriptive research method and was conducted at Holycow! Steakhouse by Chef Afit Surabaya. The research subjects include the owner, employees, and consumers. The data analysis method employed is descriptive analysis using the promotional mix. The findings of the descriptive research analysis reveal that the strategies utilized to carry out promotions through the promotional mix include advertising activities on social media platforms such as Instagram, Twitter, and WhatsApp; personal selling through face-to-face interactions with consumers; sales promotion activities involving discounts, buy-one-get-one-free offers, and customer loyalty programs; public relations through partnerships with Nestle or Coca-Cola; and Direc Marketing through friendly customer service and adherence to standard operating procedures. Consistently applying the promotional mix in the promotional strategy of Holycow! Steakhouse by Chef Afit can positively influence sales levels. Keywords: Promotional mix, Increasing Sales, Promotion Strategies.